| **Giver** | **Post** | **Date** |

| celi1210 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 30-Dec-2019 |

| Jsound996 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 21-Dec-2019 |

| Ankita1701 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 29-Nov-2019 |

| azman19 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 23-Nov-2019 |

| ottomankhan | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 31-Oct-2019 |

| kbhello | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 08-Oct-2019 |

| ConfusedSEA | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 02-Oct-2019 |

| Nelli | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 23-Sep-2019 |

| seedreama | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 20-Sep-2019 |

| agrosher | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 13-Sep-2019 |

| Un34 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Aug-2019 |

| ArseniyRUS | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 08-Aug-2019 |

| trung1610 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-Aug-2019 |

| jmwon | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-Aug-2019 |

| parthkumar1997 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 03-Aug-2019 |

| mukul2259 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 01-Aug-2019 |

| omgeyhan | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 01-Aug-2019 |

| Cosber | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 01-Aug-2019 |

| daniGMAT | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 20-Jul-2019 |

| neha22singhal | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 03-Jun-2019 |

| kokateamol | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 27-May-2019 |

| rokib hasan | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 20-May-2019 |

| jk3nnedy | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-May-2019 |

| shivangi18 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-May-2019 |

| Mustafa10 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 07-Apr-2019 |

| surbhi18196 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-Apr-2019 |

| asalam | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Mar-2019 |

| lmfaowhy1234 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 19-Mar-2019 |

| rino12 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 17-Mar-2019 |

| lethanhquyen166 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 14-Mar-2019 |